2007
DOI: 10.1111/j.1528-1167.2006.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Language Mapping: Sensitivity of Neurostimulation and Wada Testing in Epilepsy Surgery

Abstract: Summary:Purpose: Functional mapping of eloquent cortex with electrical neurostimulation is used both intra-and extraoperatively to tailor resections. In pediatric patients, however, functional mapping studies frequently fail to localize language. Wada testing has also been reported to be less sensitive in children.Methods: Thirty children (4.7 -14.9 years) and 18 adult controls (18-59 years) who underwent extraoperative language mapping via implanted subdural electrodes at the NYU Comprehensive Epilepsy Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 22 publications
3
84
0
Order By: Relevance
“…Interestingly, results of our adult studies have also suggested a greater number of positive language sites in older adults (Hamberger et al 2007). Schevon et al (2007) reported a significantly lower probability of identifying language cortex via ESM in children than in adults, with age 10 years as a sharply defined threshold. Overall, these results have been considered to reflect the development of new language foci with cortical maturation.…”
Section: Pediatric Language Mappingmentioning
confidence: 96%
“…Interestingly, results of our adult studies have also suggested a greater number of positive language sites in older adults (Hamberger et al 2007). Schevon et al (2007) reported a significantly lower probability of identifying language cortex via ESM in children than in adults, with age 10 years as a sharply defined threshold. Overall, these results have been considered to reflect the development of new language foci with cortical maturation.…”
Section: Pediatric Language Mappingmentioning
confidence: 96%
“…Furthermore, these invasive procedures require the patient to remain alert for language assessment, which is unfeasible in half of children with intractable epilepsy due to cognitive and behavioral problems. 1,5 Consequently, inconclusive results are reported in most patients younger than age 10 for ESM (up to 81%) and for IAT (50%). 5,6 In the past decade, noninvasive neuroimaging techniques, including functional magnetic resonance imaging (fMRI) [7][8][9][10][11] and magnetoencephalography (MEG), [12][13][14][15][16][17][18] have been widely used for language cerebral lateralization and mapping in adults and children.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, these methods are often not available to these patients, which may rule out surgical treatment or increase the risk of postoperative deficits. 5,30 Resting-state functional connectivity is an alternative neuroimaging approach that is not subject to the limitations described above. It is a relatively a modern method for evaluating the regional interactions that occur in the brain when a subject is not performing an explicit task.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is diminished sensitivity of neurostimulation mapping in children younger than 10 years of age, due to a higher percentage of small and unmyelinated fibers requiring an increased charge density to elicit a response to stimulation [21]. The charge density is inversely proportional to the area being stimulated and is determined by the distance between electrodes with bipolar stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The charge density is inversely proportional to the area being stimulated and is determined by the distance between electrodes with bipolar stimulation. Thus, placing the contacts closer together increases the charge density without increasing the applied current [21]. To address this possibility, we now use custom 64-contact grids with 5 mm between electrodes (Adtech Inc.) for all pediatric patients.…”
Section: Discussionmentioning
confidence: 99%